Penerapan Pelayanan Perpustakaan Sistem Automasi Terintegrasi di Universitas Medan Area - Trie Ananda; Yusniah Yusniah; Febi Fadila; Nurul Ummi,; Ummu Hoiriah Lubis (Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
In January 2017, the Medan Regional University Library (UMA) officially implemented an integrated automation system. The system is a migration from the old system that was used previously. Integrated library automation system using SLiMS Acacia version 8.3.1. With the implementation of this integrated automation, users can borrow, return, and expand their loan collection from the Medan University (UMA) branch library. Automated systems can also improve service quality and bring libraries closer to users. This study uses qualitative methods to conduct descriptive research. Descriptive research describes a picture or painting in a systematic, correct, and accurate manner, describing the facts, and the nature of the relationship between the phenomena studied. The technique of collecting data and information about all collections by researchers is in the form of observations by University librarians in the Medan area. The purpose of this research is to communicate to users what library materials the library has, provide bibliographic information, and document the characteristics of each library material, which are needed to identify and distinguish one library material from another. This will certainly help in the search for library collections, and the catalog serves as an important search tool. Keywords: UMA Library, Integrated Library System.